2001
DOI: 10.1007/s11934-001-0045-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of erectile dysfunction following radical prostatectomy

Abstract: Radical prostatectomy is the standard treatment for organ/specimen-confined prostate cancer, yet erectile dysfunction in selected series is still reported as high as 90% after this procedure. Thus, most men need adjuvant treatments to be sexually active following radical prostatectomy. These include vacuum constriction devices, intracorporeal injections of vasoactive drugs, and transurethral dilators, all of which have reported response rates of 50% to 70%. Unfortunately, long-term compliance is suboptimal, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 45 publications
0
40
0
2
Order By: Relevance
“…7,8,10 In our early penile rehabilitation program, the VCD was the preferred erectile aid. The advantage of VCD is that the erections produced are independent of endogenous vasoactive substance such as nitric oxide (NO) production, which is impaired by nerve damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8,10 In our early penile rehabilitation program, the VCD was the preferred erectile aid. The advantage of VCD is that the erections produced are independent of endogenous vasoactive substance such as nitric oxide (NO) production, which is impaired by nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…With this approach, the integrity of the cavernous tissues may be maintained, which can potentially prevent cavernous tissue fibrosis from precluding the return of spontaneous erections or decreasing the response to erectile aids. [7][8][9] Vacuum constriction devices (VCD) have been successfully used in a variety of patients with organic ED. 10 Its use included those patients treated for prostate carcinoma with either RP or radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ED after prostatectomy is generally treated symptomatically, as needed when intercourse is anticipated. 5,6 However, early regular use of intracavernosal alprostadil injections, in an uncontrolled study, has been shown to improve the recovery rate of spontaneous erections after nerve-sparing radical retropubic prostatectomy. 7 Despite this benefit, pain, complications and inconvenience detract from the willingness of patients to use intracavernosal injections regularly.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Provoking an artificial erection during this time is thought to minimize cavernous tissue fibrosis, leading to potentially improved erection quality or decreased need for supplemental agents. These early observations have led to the development of post-RP penile rehabilitation protocols that employ various combinations of oral [12][13][14] and intercavernosal agents, 15 as well as the vacuum erection device (VED). 16,17 Given recent advances in surgical technique, it is logical that careful examination should be dedicated to the establishment and validation of a post-RP protocol that improves EF outcomes.…”
Section: Introductionmentioning
confidence: 99%